Infant-Feeding Patterns and the Effects of Early Introduction to Formula and Solid Foods on Childhood Overweight or Obesity among 10-Years-Olds in a Low Socioeconomic Area of Lebanon: An Exploratory Analysis - Haider Mannan; Yonna Sacre; Randa Attieh; Dany Farah (MDPI AG, 2022)
In Lebanon, there has been an alarming increase in childhood overweight and obesity. In addition, most mothers do not meet the WHO recommendation that infants should be introduced to formula or solids only during the second half of their first year. Because the study population, Burj Hammoud, which is a low socioeconomic district, is small, we performed an exploratory analysis of infant feeding patterns and the effects of introducing formula and solids within six months, respectively, on childhood overweight/obesity among 10-year-old children. A total of 101 mothers were recruited from seven intercommunity dispensaries located across the district. Descriptive, univariate and multivariate logistic regression analyses were performed. There were 86.1% infants initiating breastfeeding, 18% exclusively breastfeeding at 6 months of age, 67.1% and 52.6% starting formula and solids by 6 months, respectively, and 53.5% becoming overweight/obese by the age of 10 years. Working mothers were significantly less likely to introduce formula but not solids within the first six months of infancy. Based on two case-control studies, after controlling for maternal employment, there were 2.278- and 1.511-fold significantly higher odds of introducing solids and formula before the age of 6 months compared with after the age of 6 months, respectively, for the overweight/obese individuals among 10-year-olds. Future research should focus on conducting a larger study by incorporating other low socioeconomic regions to confirm these relationships.